Peran Dan Tantangan Lembaga Arbitrase Syariah Dalam Menyelesaikan Sengketa Bisnis Syariah - Syahfitra, Nofri Ramadhani; Winario, Mohd; Khairunisa, Madona; Syam, Zulkharil Hadi (EL-EMIR Institute, 2024)
This research examines the role and challenges faced by sharia arbitration institutions in completing sharia business settlements. As an alternative to out-of-court settlement, sharia arbitration offers a solution that complies with sharia principles and Islamic law. This research uses qualitative methods with a literature study approach and in-depth interviews with practitioners in the field of sharia arbitration. The research results show that sharia arbitration institutions play an important role in providing legal certainty and justice for disputing parties, especially in the context of sharia business. However, there are a number of challenges that hamper the effectiveness of this institution, including a lack of public understanding and trust in sharia arbitration, limited competent human resources, and regulatory constraints that do not fully support the development of this institution. Therefore, further efforts are needed to increase socialization, training and regulatory adjustments to strengthen the role of sharia arbitration institutions in completing the recovery of sharia business in Indonesia. The research results show that the Sharia Arbitration Institution plays an important role in providing dispute resolution mechanisms that are in accordance with sharia principles, maintaining the trust of sharia business actors, and reducing the burden on district courts. However, the challenges faced include a lack of public understanding and awareness about sharia arbitration, limited competent human resources, and a lack of harmonization of regulations that support the operationalization of these institutions.